Associação dos alelos do HLA CLASSE II (DRB1 e DQB1) com as características clínicas e hematológicas na anemia falciforme - Ponte, Mauriclécio Franco (2014)
Sickle cell anemia (SCA) is an inherited disease, often, but not exclusively, in individuals of African origin. In the black Brazilian population there is a prevalence from 0.1 to 0.3% tending to affect an ever larger portions due to miscegenation. Specific alleles of the HLA system and may influence the risk of appearance of clinical symptoms in patients with SCA, whereas their genotypes may serve as useful markers in identifying the risk for certain clinical manifestations. The study was a randomized-case control in order to evaluate the association of alleles of the HLA class II system with clinical features and hematological parameters of patients with SCA. The genotyping were performed for the DRB1 and DQB1 loci from 62 individuals diagnosed with SCA and 86 healthy individuals (HbA2) used as controls. Allele frequencies (Fa) were obtained by direct counting and calculated by the formula Fa = a / 2n. In the group with SCA the five most common HLA-DRB1 alleles were DRB1*04 (16.9%), DRB1*01 (12.9%), DRB1 * 08 (12.1%), DRB1 * 07 and DRB1 * 11 (both 11.3%), which represent 64.5% of the total variability of the 13 analyzed specificities. The three most frequent alleles were HLA-DQB1 DQB1*03 (45.2%), DQB1*05 (18.5%) and DQB1*06 (16.9%), corresponding to 80.6% of the total variability of the 5 analyzed specificities. For the control group the five most frequent HLA-DRB1 alleles were DRB1*04 (16.3%), DRB1*13 (15.1%), DRB1*08 and DRB1*15 (both 11.6%) and DRB1*07 (8.1%), which represent 62.7% of the total variability of the 13 analyzed specificities. The HLA-DQB1, the three most frequent alleles were DQB1*03 (32.0%), DQB1*06 (22.7%) and DQB1 *05 (19.2%), corresponding to 73.9% of the total variability of the 5 analyzed specificities. Regarding cerebrovascular accident (CVA), the DRB1*15 and DQB1*06 (p = 0.0033 and p = 0.0077, respectively) showed a high frequency in patients who developed stroke. For acute chest syndrome (STA), the DRB1*01 (p = 0.0398) and DQB1*06 (p = 0.0057) were the most frequent allele in the group STA, while the DRB 1*01 alleles (p = 0.03980) and DQB1 * 05 (p = 0.0446) were more frequent in patients without STA. There were no significant associations with painful vaso-occlusive crises. Total hemoglobin and hematocrit (p = 0.045 and 0.0036, respectively), and fetal hemoglobin (HbF) (p = 0.024) were the only hematological parameters that had significant association with the DQB1 locus being responsible for this association. Regarding HbF, the DQ02 and DQ06 alleles were associated with lower and higher levels, respectively, of this hemoglobin fraction in the patients studied (p = 0.015). Our results provide the first evidence that the HLA genes are involved in modification of the clinical course or onset of complications in individuals with SCA in Brazil.